The evolution of modern grand strategic thought - Milevski, Lukas (Oxford : Oxford University Press, 2016)
In strategic studies and international relations, grand strategy is a frequently-invoked concept. Yet, despite its popularity, it is not well understood and it has many definitions, some of which are even mutually contradictory. This state of affairs undermines its usefulness for scholars and practitioners alike. Lukas Milevski aims to remedy this situation by offering a conceptual history of grand strategy in the English language, analysing its evolution from 1805 to the present day in the writings of its major proponents.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 14, 2016).
Keywords: International relations; Strategy